BIOREMEDIATION OF PAHS CONTAMINATED SOIL BY UTILIZING AN INDIGENOUS EARTHWORM SPECIES, PERIONYX EXCAVATUS - SUBASH, N; SASIKUMAR, C (International Journal of Pharma and Bio Sciences, 2014)
Polycyclic aromatic hydrocarbons (PAHs) are insurmountable pollutant that contaminates the soil and occurs frequently. The restoring of contaminated soil fertility is pricey and time intense process. Earthworms accelerate the removal of PAHs from contaminated soil by feeding and get better the soil structure and aeration of the soil. The main aim of this research work is to utilize the earthworm viz., Perionyx excavatus for the taking away of PAHs from the soil and restoring the soil fertility. During this study, the mortality rate of P. excavatus was 2% which means P. excavatus can tolerate the PAHs compounds present in the experimental medium. The worm worked soil showed significant increase in total nitrogen, total phosphorus and total potassium and total magnesium than worm un-worked soil. It is obvious from the results that the earthworm viz., Perionyx excavatus may perhaps be used to remove the PAHs from soil and restore the soil fecundity through their excretory creation.